Analisis Perbandingan Sistem Pendidikan Negara-negara Maju Sebagai Komparasi Kemajuan Pendidikan di Indonesia - Nurrijal, Nurrijal (Jurnal Biologi Babasal, 2024)
This article examines the comparison of educational treatments in several developing countries through the analysis of the input, process, and output aspects of education. The study employs a comparative method to compare education policies and practices in developed countries. It is conceptual research that gathers data from various sources, including government reports, academic research, and relevant literature such as books, internet sources, and journals. The analysis is conducted by collecting and analyzing information to understand the differences in education systems, the quality of education, and the factors influencing educational output. The study aims to provide deep insights into the construction of educational system development in Indonesia, focusing on the influence on educational output. Education is a domain influenced by various factors, resulting in differences in educational outcomes and quality among countries. The analysis results indicate significant variations in education policies, curricula, teaching methods, and educational resources in the compared countries. This research encourages studying the education systems and implementation in institutions or other countries with the aim of absorbing positive information to improve and enhance education in Indonesia. Considering the analysis results, this article presents an important contribution to the thinking and renewal of education in Indonesia, highlighting areas that need improvement and models that can be adopted to improve overall education quality.